The Relationship Between The Interpersonal Communication Of Father With Prosocial Behavior Of Children Age 4-6 Years In Semarang - Kiki Anna, Dwi (BELIA: Early Childhood Education Papers, 2017)
Important prosocial behavior developed in the pattern of family care is seen from the more modern times of development and increasing juvenile delinquency. Parenting patterns can lead children to prosocial behavior and anti social behavior. Parents are not only responsible for the growth of children but also in building relationships between family members. A relationship certainly can not be separated from the communication between members. Through the family, parents' interpersonal communication, especially the father is able to give influence to the formation of a child's attitude, especially his prosocial behavior. This study aims to determine whether there is a relationship between the father's interpersonal communication with the behavior of prosocial children aged 4-6 years in Semarang. The method used in this study is quantitative correlational is research that aims to find a relationship between two or more aspects. Data collection in this study using two scales, namely the scale of interpersonal communication and the scale of prosocial behavior. The population of this study is all fathers who have children aged 4-6 years in Semarang city that carried out in three areas namely Tambak Aji, Kalimasada and Bandarharjo with sampling techniques as many as 100 fathers. Methods of data analysis in this study using product moment correlation analysis. The results of this study indicate there is a positive relationship between father's interpersonal communication with child's prosocial behavior obtained from rxy = 0.572 with significance value p <0.05. The direction of positive relationship shows the higher interpersonal communication father, the higher the behavior of prosocial children aged 4-6 years in Semarang. Conversely, the lower the father's Interpersonal communication, the lower the child's prosocial behavior.